Retrograde Amnesia – A Question of Disturbed Calcium Levels? - Montag, Dirk (Frontiers in Cellular Neuroscience, 2021)
Retrograde amnesia is the inability to remember events or information. The successful acquisition and memory of information is required before retrograde amnesia may occur. Often, the trigger for retrograde amnesia is a traumatic event. Loss of memories may be caused in two ways: either by loss/ erasure of the memory itself or by the inability to access the memory, which is still present. In general, memories and learning are associated with a positive connotation although the extinction of unpleasant experiences and memories of traumatic events may be highly welcome. In contrast to the many experimental models addressing learning deficits caused by anterograde amnesia, the incapability to acquire new information, retrograde amnesia could so far only be investigated sporadically in human patients and in a limited number of model systems. Apart from models and diseases in which neurodegeneration or dementia like Alzheimer's disease result in loss of memory, retrograde amnesia can be elicited by various drugs of which alcohol is the most prominent one and exemplifies the non-specific effects and the variable duration. External or internal impacts like traumatic brain injury, stroke, or electroconvulsive treatments may similarly result in variable degrees of retrograde amnesia. In this review, I will discuss a new genetic approach to induce retrograde amnesia in a mouse model and assess the relation of calcium alterations and retrograde amnesia. Recently, we observed that neuronal loss of neuroplastin resulted in retrograde amnesia specifically for associative memories. Neuroplastin is tightly linked to the expression of the main Ca2+ extruding pumps, the plasma membrane calcium ATPases (PMCAs). Neuronal loss of neuroplastin may alter Ca2+ signaling cascades and, thereby, interfere with the retrieval and storage of associative memories. The possibility to elicit retrograde amnesia in a controlled manner allows to investigate the underlying mechanisms and may provide a deeper understanding of the molecular and circuit processes of memory.